ANALISIS KEANDALAN EMBUNG SELOPAMIORO DALAM MEMENUHI KEBUTUHAN AIR BAKU DAN IRIGASI DAERAH IMOGIRI BANTUL - Sri Amini Yuni Astuti; Agus Budi Satriyo (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Management of water sources in the Imogiri Region of Bantul Regency still needs to be improved. Although there are several springs in the area, water availability can still not meet the community’s water needs. Therefore, the solution needed is a problem solved to get a good water management system so that the wheels of life and the community’s economy can run well. One of them is to build a water reservoir as a small dam. With this Embung Selopamioro, it is hoped that the rainwater that falls in this region can be accommodated and used for community needs. The study was conducted with several analyses of the capacity of the small dam with three comparisons: analysis of water availability, analysis of water demand, and analysis of topographic characteristics. Small dam reliability is analyzed by simulating a reservoir water balance and the level of reservoir reliability in meeting the community’s water needs. The maximum capacity of the small dam is 9.317,72 m3, with a living storage capacity of 8.979,71 m3 and a dead storage capacity of 338,01 m3. The water requirement that can be met is the irrigation demand of 9,71 ha of rice field with 667.683,556 m3, and the raw water demand for 1.318 people is 24.465 m3. The level of small dam reliability for optimizing irrigation water demand with an area of 9,71 ha rice field and raw water demand with a population of 1.318 people has the lowest value of 51%.